(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study describes the representation of Indonesian Generation Z's national identity on IDN Times' Instagram. The results show that Indonesian Generation Z prefers content that combines traditional cultural elements with modernity, in creative and easily accessible forms, such as through social media, short videos, and digital platforms. The research design used mixed methods, namely by conducting quantitative content analysis on Indonesian Generation Z's national identity content on IDN Times' Instagram from January to September 2024. Qualitative data were obtained through in-depth interviews with 20 Generation Z individuals aged 18 to 25, representing all provinces in Indonesia. The qualitative approach was carried out using virtual anthropology methods, focusing on how information and communication technology influences social life, culture, and individual identity in virtual environments. Three elements studied include the representation of traditional symbols, local-global hybridization, and digital activities. Content featuring traditional music with a modern touch, or memes that reflect Indonesia's rich culture in a lighthearted and humorous manner, is more engaging. The presence of social media has become a primary space for expressing, criticizing, and capturing global issues. Generation Z also tends to support environmentally friendly products and engage in activities that can reduce negative impacts on the Earth. They use social media for positive change to maintain their Indonesian identity, but still adapt to global trends.